PENGARUH STRES KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. SINARMAS MULTIFINANCE CABANG MALANG PADA MASA PANDEMI COVID-19 - Magda Magda (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The purpose of this study was to determine the effect of work stress, motivation, and compensation on employee performance at PT. Sinarmas Multifinance Malang branch. The population in the study were all employees of PT. Sinarmas Multifinance Malang branch is 54 employees. The sample was determined based on the multiple linear regression analysis method. Based on saturated sampling all employees are used as samples. This study uses quantitative types, and Non Probability Sampling data analysis techniques used are questionnaire validity test instruments, reliability tests, classical assumptions test using residual normality test, multicollinearity test, heteroscedasticity test, linearity test, descriptive analysis, multiple linear regression analysis, coefficient of determination, and hypothesis testing using t test and f test. The results showed that work stress was positive and had no significant effect on employee performance, motivation and compensation were positive and significant on employee performance. Work stress, motivation and compensation have a joint effect on employee performance.